Ordinance no. 56, §§ 15-16, Wenatchee City Council (1902) (Wenatchee, Washington). - (:unkn) unknown (My University, 1902)
No person, except a police officer shall have or carry any bowie knife, pistol, sling shot, sand bag or other weapon concealed on or about his or her person; or fire or discharge any gun, rifle, fowling piece, pistol or other firearm within the limits of the town without a permit from the mayor and marshal.
Keywords: CARRY - CONCEALED